1989
DOI: 10.1029/ja094ia09p11843
|View full text |Cite
|
Sign up to set email alerts
|

Damping of magnetospheric cavity modes: A discussion

Abstract: Impulsive changes in the solar wind can deposit energy into magnetospheric cavity modes. We discuss the coupling of cavity modes to the field line continuum, and show that the time scales for dissipative phase mixing and mode conversion to kinetic Alfvén waves in the magnetosphere are long compared with lifetimes of MHD wave events with periods that vary continuously with radial distance. Therefore the ultimate dissipative sink for cavity mode energy should be the ionosphere. For model magnetospheres in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
(46 reference statements)
1
14
0
Order By: Relevance
“…Previous works placed the inner boundary at the plasmapause (for example, the box model used by Southwood (1985, 1986) and the dipole model used by Lee and Lysak (1989)) or at the ionosphere (Fujita and Patel, 1992). These theoretical studies examined the effect of the ionospheric dissipation on coupled oscillations (Allan et al, 1986a;Krauss-Varban and Patel, 1988;Allan and Poulter, 1989) and the ionospheric transmission property (Kivelson and Southwood, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Previous works placed the inner boundary at the plasmapause (for example, the box model used by Southwood (1985, 1986) and the dipole model used by Lee and Lysak (1989)) or at the ionosphere (Fujita and Patel, 1992). These theoretical studies examined the effect of the ionospheric dissipation on coupled oscillations (Allan et al, 1986a;Krauss-Varban and Patel, 1988;Allan and Poulter, 1989) and the ionospheric transmission property (Kivelson and Southwood, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…These discrete cavity modes decay by coupling to the transverse Alfven waves on L shells where the frequency of the field line resonances matches that of the cavity mode. They can also decay by depositing Poynting flux from the wave into the low latitude ionosphere (Allan and Poulter, 1989) or by leaking energy into the magnetotail. In this latter case, the cavity may be better approximated as a wave guide (Samson and Harrold, 1992) with the azimuthal wavelength imposed by the source.…”
Section: Introductionmentioning
confidence: 99%
“…They interpreted this low damping rate as evidence that the wave was driven by a compressional magnetospheric cavity mode stimulated by an earlier sudden pressure pulse in the solar wind. Numerical analyses (Allan and Poulter, 1989;Allan and McDiarmid, 1989) have provided insight into the relation between damping produced by direct energy losses to the ionosphere and damping arising from coupling to the continuous spectrum of field line resonances. Their analysis supports the interpretation of Crowley et al (1987).…”
Section: Introductionmentioning
confidence: 99%
“…The time scales of the packeting clearly relate to the described mechanism. Allan et al (1985) and Allan and Poulter (1989) have shown amplitude modulations near a resonance as a result of beating due to the frequency mismatch between the driving cavity mode and the natural Alfve n frequency on one particular ®eld line. In contrary the interaction presented in this work is caused by the frequency mismatch between two azimuthal perturbations on two neighboring ®eld lines.…”
Section: Possible Misinterpretationsmentioning
confidence: 99%